Triterpenoids with anti-proliferative effects from the seeds of Peganum harmala L. (June 2020) - Li, Haiyan; Wang, Zhe; Wang, Yihai; Xu, Jingwen; He, Xiangjiu
Abstract: Three undescribed lupane-type triterpenoids (1–3), three undescribed oleanane-type triterpenoids (4–6), and ten known pentacyclic triterpenoids (7–16) were isolated from the seeds of Peganum harmala L. (Zygophyllaceae). Their structures were elucidated using various spectroscopic methods (IR, HR-ESI-MS, 1D, and 2D NMR). All the triterpenoids were screened for anti-proliferative activity against HeLa, HepG2, and SGC-7901 cells using the MTT method. Except compounds 1, 2, and 13, all the other triterpenoids exhibited potent cytotoxic activities against tumour cells. Compounds 3, 6, and 15 inhibited the proliferation of HeLa cells in a dose-dependent manner, as observed by the colony formation assay. When HeLa cells were treated with different doses of compounds 3, 6, and 15, the cell nuclei changed shape to a crescent form and were condensed and fragmented, as observed by Hoechst 33258 staining. Additionally, these three triterpenoids induced the apoptosis in HeLa cells, which was detected by Western blot analysis. Graphical abstract: Six previously undescribed triterpenoids along with ten known congeners were isolated from the seeds of Peganum harmala . L. Most of them showed potential antitumor activity. Image 1 Highlights: Six undescribed and ten known triterpenoids were isolated from Peganum harmala L. Structures were elucidated through IR, 1D, 2D NMR and HR-ESI-MS. Some triterpenoids exhibited potent anti-proliferative activities. The primary anti-proliferative mechanisms of the bioactive triterpenoids were investigated.